The Mach-Zehnder Interferometer Based on Silicon Oxides for Label Free Detection of C-reactive Protein (CRP) - Hong, Jongin; Yoon, Daesung; Kim, Tae Song (KOREAN BIOCHIP SOCIETY-KBCS, 2009)
The C-reactive protein (CRP) is a very important inflammation biomarker and a major predictor of cardiovascular disease (CVD) in human. We demonstrated here on a new approach to determine the binding of label free CRP to monoclonal anti-CRP using the Mach-Zehnder interferometer based on silicon oxides with the detection limit of 1 ng/mL or even less at the operating wavelength of 1,550 nm. The building block, single-mode waveguide of total internal reflection, was precisely designed using a finite element method (FEM) and so we suggested the guideline of micro-fabrication to achieve it. We also firstly introduced the calixcrown self-assembled monolayers (SAMs), which guaranteed the activity of capture proteins and the correct orientation, to immobilize the monoclonal anti-CRP on PECVD silicon oxides into the biosensors based on the interaction of the evanescent field of the guided light with the surrounding environment.
Keywords: ANTIBODY-ANTIGEN INTERACTION; ELECTRICAL DETECTION; IMMUNOSENSORS; SENSITIVITY; DISEASE; MARKER